Synthesis and Characterization of Some New Nucleoside Analogues from Substituted Benzimidazole and Evaluation of Their Biological Activities - M. Al-Mouamin, Thanaa; Kh. Kadhim, Ahmed (Iraqi Journal of Science, 2023)
This research includes the synthesis of some new nucleoside analogues via 1,3-dipolar cycloadditon reaction starting with 1,3,4,6- Tetra- O-benzoyl –2 – azido-2-deoxy- β – D- fructofuranose (F3) which was prepared in three steps ,protection(benzoylation ) , bromination and azotation ((F1-F3) from D- fructose as sugarmoiety while the base moiety , 2-substituted benzimidaole derivatives (A1-A5)were synthesized by condensation of O-phenylenediamine with different aromaticaldehyde .Nucleophilic substitution of propargyl bromide with benzimidaole derivatives (gavethe N- substituted compounds (B1-B5) which were reacted with azido sugar through1,3- dipolar cycloadditon reaction to give nucleoside analogues (C1-C5) .Debloking of these nucleoside using sodium methoxide in methanol afforded ourtarget the free nucleoside analogues (D1-D5).All prepared compound were identified by FT-IR and some of them with 1H-NMRand 13C-NMR. The synthesized compounds (D1-D5) were screened for their in-vitroantibacterial and antifungal activity.